Mesenteric lymph node abscesses due to Escherichia coli in a cat. Issue 4 (2nd June 2022) - Sakai, Kosei; Kanegi, Ryoji; Nabetani, Tomoyo; Tanaka, Toshiyuki; Shimamura, Shunsuke; Shimada, Terumasa; Sugiura, Kikuya; Hatoya, Shingo
Abstract: A 3‐year‐old, castrated male mixed‐breed cat presented with an almost 2‐year history of chronic loose stools. On radiography and ultrasound examination, there were two masses in the centre of the abdomen. Contrast‐enhanced computed tomography revealed that the masses were enlarged mesenteric lymph nodes with fluid accumulation. Percutaneous lesion drainage yielded pus‐like fluid. Fluid cytology revealed numerous neutrophils and Gram‐negative rods. Pus culture identified Escherichia coli as the causative organism. Consequently, mesenteric lymph node abscesses were definitively diagnosed. Since computed tomography showed that the abscesses adhered to the surrounding tissues, it was difficult to remove them surgically. With drainage and antimicrobial therapy, the mesenteric lymph nodes gradually decreased in size. However, loose stools persisted. The cat's diet was changed to a hydrolysed diet, and the clinical symptoms improved, suggesting food‐responsive enteropathy. This may be an underlying disease of lymph node abscesses. Lymph node abscesses limited to the mesenteric lymph nodes rarely occur in veterinary medicine, and this is the first report in cats.